PTU-039 Should Mr Enterography Be The Preferred Surveillance Modality Compared To Small Bowel Capsule Endoscopy In Peutz-jegher's Syndrome?. (9th June 2014) - Rameshshanker, R; Gupta, A; O'Rourke, A; Clark, S; Phillips, R; Fraser, C
Abstract : Introduction: Peutz-Jeghers syndrome (PJS) causes multiple hamartomatous polyp formation throughout the gastrointestinal tract. Large polyps within the small bowel (SB) may cause complications and morbidity including obstruction, bleeding, an increased risk of cancer and post surgical adhesional disease. Regular surveillance and removal of large polyps are important to prevent complications from occurring. Methods: The aim of our study was to assess the utility of SB capsule endoscopy (SBCE) compared with MR enterography (MRE) for the detection of small bowel PJS polyps. We performed a retrospective review of all adult PJS patients under the care of the St Mark's Polyposis Registry between 2006–2012. Participants' MRE and SBCE findings, enteroscopy reports and case notes were reviewed. Polyps >10 mm were regarded as clinically relevant. Large polyps (>15mm) resected at push enteroscopy (PE), double balloon enteroscopy (DBE) or intraoperative enteroscopy (IOE) were correlated in terms of size, location, number and need for resection with both MRE and SBCE findings. Results: 95 patient episodes involving 83 patients (median age 38yrs, 60% female) were included. SBCE was performed in 78 patient episodes, either alone (n = 29) or prior to MRE (n = 49). Reasons for MRE post SBCE were: previous study involvement (n = 19), post-polypectomy reassessment (n = 10), persistent symptoms (n = 9) and confirmation of significant polyp findings (n = 11). There was no significant difference between patients in whom >10 mm polyps were detected (77 vs. 106 for SBCE and MRE, respectively; p = 0.124). In 6 patients, large polyps (>15 mm) not detected at SBCE, were identified at MRE. Endoscopic removal of large polyps was performed during 63 patient episodes. 22 patients episodes did not require polypectomy. DBE's were incomplete due to failure of deep intubation in 7 patients (19%) but 4 of these patients subsequently underwent laparoscopic assisted DBE and successful polypectomy. Concordance with DBE findings for polyp size for SBCE vs. MRE was 61% and 79%, respectively (p = 0.18). Concordance with DBE findings for polyp location for SBCE vs. MRE was 79% and 92%, respectively (p = 0.76). Conclusion: MRE appears at least as effective as the current iteration of SBCE for small-bowel polyp surveillance in adults with PJS. MRE may be less prone to missing large polyps and more accurate in polyp size assessment and localisation and in post-polypectomy reassessment of the SB. Disclosure of Interest: None Declared.